Análise dos pressupostos teóricos presentes no manual de filosofia da educação: os grandes problemas da pedagogia moderna (1942) de Theobaldo Miranda Santos - Calixto, Jaqueline de Andrade (2016)
This study addresses an analysis of the great problems of moderm pedagogy (Manual de filosofia da educação: os grandes problemas da pedagogia moderna) from Theobaldo Miranda Santos (1904-1971), published in 1942 by the Bonffoni Editions with the objective of understand the educational thinking of this intellectual presente in this work with the modern pedagogy. Under the methodological theoretical perspective this study approaches from thehistory of pedagogycal ideas and the and History of Intellectuals inspired by studies Saviani Vieira, Daros, Almeida Filho e Souza. The clipping established for this research addresses the decades of 1920 to 1940 with the objective of understand the catholics intellectual’s moviment in defense of christian pedagogy and and the competition for them against the established pedagogy advocates of the New School. The educational debatein the begin of 1920 is heated by the catholics attempt to appropriate again the school space. One of the strategy of the institution was to publicate school’s manuals to teacher’s formations with the intention of disclose the catholic-christian doctrine. In addition to these arrests sought to consider the role of these intellectuals with the Braziliam association of education - A.B.E. The context from the education performance of Theobaldo Miranda Santos in the servisse of braziliam education. The understanding of the trajectory of our intellectual enabled us to move forward in the investigation to know the historical time of insertion of the “manual de Filosofia da Educação” now analyzed in this work. The intelectual published a total of 150 titles covering the levels of primary, secondary and higher education. Converted to catholicism in the late of 1920 achieved a prominent place as publicist for the production of textbooks and prestige in the Brazilian intellectual field. Defender of thomistic philosofy. It stated that the philosophical speculations postulated by St. Thomas Aquino was not overtaken by modern pedagogy as advocated John Dewey and the pragmatists. He worked in the administrative offices at the Getulio Vargas government period alongside Alceu Amoroso Lima. Some missives exchanged between Tristão de Athayde and Theobaldo M. Santos collaborate for the reasoning of the object of this research. We left for the manual description itself analyzing some categories established by the author to describe the philosophical basis of education and the philosophical problems of education. We conclude toward an analysis of modern pedagogy and its dismemberment at the New School, also considered whether a synthesis of Thomistic philosophy discussed in the manual by our author.